2008
DOI: 10.1128/jvi.00040-08
|View full text |Cite
|
Sign up to set email alerts
|

Role for the L1-52/55K Protein in the Serotype Specificity of Adenovirus DNA Packaging

Abstract: The packaging of adenovirus (Ad) DNA into virions is dependent upon cis-acting sequences and trans-acting proteins. We studied the involvement of Ad packaging proteins in the serotype specificity of packaging. Both Ad5 and Ad17 IVa2 and L4-22K proteins complemented the growth of Ad5 IVa2 and L4-22K mutant viruses, respectively. In contrast, the Ad5 L1-52/55K protein complemented an Ad5 L1-52/55K mutant virus, but the Ad17 L1-52/55K protein did not. The analysis of chimeric proteins demonstrated that the N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Both the full-length and 40-kDa bands disappear and are replaced by higher-molecular-mass species in electrophoresis performed in the absence of ␤-mercaptoethanol, suggesting the formation of disulfide-linked homodimers mediated by the only Cys residue (Cys24) in L1 52/55k (9,22). The 34-kDa band has been proposed to originate by an additional cleavage at the N terminus, because it does not react with antibodies against either residues 9 to 22 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) or 402-415 in L1 52/55k, and its electrophoretic mobility is not sensitive to nonreducing conditions, a finding consistent with the absence of Cys24 (9,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the full-length and 40-kDa bands disappear and are replaced by higher-molecular-mass species in electrophoresis performed in the absence of ␤-mercaptoethanol, suggesting the formation of disulfide-linked homodimers mediated by the only Cys residue (Cys24) in L1 52/55k (9,22). The 34-kDa band has been proposed to originate by an additional cleavage at the N terminus, because it does not react with antibodies against either residues 9 to 22 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) or 402-415 in L1 52/55k, and its electrophoretic mobility is not sensitive to nonreducing conditions, a finding consistent with the absence of Cys24 (9,22).…”
mentioning
confidence: 99%
“…L1 52/55k binds to the viral packaging sequence in vivo and to the putative packaging ATPase IVa2 in vitro (17-19). L1 52/55k contributes to the specificity of packaging, possibly via an interaction with capsid protein IIIa (12,20). Furthermore, L1 52/55k has been reported to bind nonspecifically to DNA and to interact with pVII and its mature form VII in infected cells (21).…”
mentioning
confidence: 99%
“…In an earlier study, we found that the Ad17 L1-52/55K protein was not able to substitute for the Ad5 L1-52/55K protein in an infection with an Ad5 L1-52/55K mutant virus (28). In contrast, both the Ad17 IVa2 and L4-22K proteins were able to functionally substitute for their Ad5 counterparts (28). These results suggested the possibility that the serotype specificity is determined by the interaction be-tween the L1-52/55K protein and the Ad packaging domain and/or capsid components during virus assembly.…”
mentioning
confidence: 99%
“…The pseudopackaging of the genome of one Ad serotype into the capsid of another Ad serotype is generally inefficient except with highly related viruses (18). The Ad IVa2 and L1-52/55K proteins have been implicated in the serotype specificity of Ad DNA packaging (28,32). In an earlier study, we found that the Ad17 L1-52/55K protein was not able to substitute for the Ad5 L1-52/55K protein in an infection with an Ad5 L1-52/55K mutant virus (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation